2021
DOI: 10.3390/ijms22168811
|View full text |Cite
|
Sign up to set email alerts
|

JI017 Attenuates Oxaliplatin-Induced Cold Allodynia via Spinal TRPV1 and Astrocytes Inhibition in Mice

Abstract: Oxaliplatin, a well-known chemotherapeutic agent, can induce severe neuropathic pain, which can seriously decrease the quality of life of patients. JI017 is an herb mixture composed of Aconitum carmichaelii, Angelica gigas, and Zingiber officinale. Its anti-tumor effect has been reported; however, the efficacy of JI017 against oxaliplatin-induced allodynia has never been explored. Single oxaliplatin injection [6 mg/kg, intraperitoneal, (i.p.)] induced both cold and mechanical allodynia, and oral administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
0
9
0
1
Order By: Relevance
“…Oxaliplatin increases cytosolic Ca 2+ by increasing the expression of nonselective cation channel TRPV1 in DRG neurons, thus increasing sensory neurons' excitability. Silencing or blocking TRPV1 reduced both oxaliplatin and paclitaxel induced neuropathic pain (185)(186)(187)(188), which is indirect evidence that mitochondrial Ca 2+ buffering is also involved in chemotherapy-induced neuropathic pain. A role for MCU in mechanical allodynia has been found in mice with painful diabetic neuropathy.…”
Section: Ca 2+ Bufferingmentioning
confidence: 81%
“…Oxaliplatin increases cytosolic Ca 2+ by increasing the expression of nonselective cation channel TRPV1 in DRG neurons, thus increasing sensory neurons' excitability. Silencing or blocking TRPV1 reduced both oxaliplatin and paclitaxel induced neuropathic pain (185)(186)(187)(188), which is indirect evidence that mitochondrial Ca 2+ buffering is also involved in chemotherapy-induced neuropathic pain. A role for MCU in mechanical allodynia has been found in mice with painful diabetic neuropathy.…”
Section: Ca 2+ Bufferingmentioning
confidence: 81%
“…The mice were habituated to the arena for 30 min prior to testing. Von Frey filaments (Stoelting, WI, United States) of different forces (.02–2 g) were then used to determine the 50% withdrawal threshold, as previously described ( Lee et al, 2021 ). Briefly, the filaments were applied perpendicular to the plantar surface of the filament for up to a maximum of 5 s or until licking, flinching, or withdrawal of the paw occurred.…”
Section: Methodsmentioning
confidence: 99%
“…For many years, our group has been focusing on CIPN to understand its underlying mechanism of action and to find an effective drug [19,[21][22][23][24]. In particular, we demonstrated that the analgesic effect of oxaliplatin-induced pain could be mediated by activation of the central descending pain-inhibitory system, such as the serotonergic and noradrenergic pathways [19,22,24].…”
Section: Introductionmentioning
confidence: 94%
“…All behavioral tests were conducted as described in our previous study [21,22]. Cold and mechanical allodynia were measured and quantified using acetone-drop and von-Freyfilament tests, respectively.…”
Section: Behavioral Testsmentioning
confidence: 99%